PELAKSANAAN EKSTRAKURIKULER BERNYANYI DI SMA NEGERI 3 KOTA SOLOK - Rilvi Handani; Erfan Erfan; Ardipal Ardipal (FBS Universitas Negeri Padang, 2018)
Abstract This article aimed to describe the Extracurricular Implementation of Singing in SMA Negeri 3 Kota Solok, The type of the study was qualitative with the descriptive method of analysis. The object of the study was the students involved in the singing extracurricular activities. The main instrument in the research was the researcher himself that was assisted with supporting instruments such as stationeries and photo cameras. Data collection was done through observation, interview, documentation and literature study. The steps taken in analyzing data were collecting data, identifying data, classifying data and describing data. The results showed that singing extracurricular activity in SMA N 3 Solok run well. Thus, the process of performing singing extracurricular has reached a level of success. Although, at the first, students have understood basic vocal techniques but students have not understood the technique of singing well and how to sing songs and master the song. Keywords: Implementation, Extracurricular, Singing.